Simulation of water-gas shift membrane reactor for integrated gasification combined cycle plant with CO2 capture - Lotrič, Andrej (Strojniški vestnik, 2011)
The effectiveness of energy conversion and carbon dioxide sequestration in Integrated Gasification Combined Cycle (IGCC) is highly dependent on the syngas composition and its further processing. Water gas shift membrane reactor (WGSMR) enables a promising way of syngas-to-hydrogen conversion with favourable carbon dioxide sequestration capabilities. This paper deals with a numerical approach to the modelling of a water gas shift reaction (WGSR) in a membrane reactor which promotes a reaction process by selectively removing hydrogen from the reaction zone through the membrane, making the reaction equilibrium shifting to the product side. Modelling of the WGSR kinetics was based on Bradford mechanism which was used to develop a code within Mathematica programming language to simulate the chemical reactions. The results were implemented as initial and boundary conditions for the tubular WGSMR model designed with Aspen Plus software to analyze the broader system behaviour. On the basis of selected boundary conditions the designed base casemodel predicts that 89.1% CO conversion can be achieved. Calculations show that more than 70% of carbon monoxide conversion into hydrogen appears along the first 40% of reactor length scale. For isothermal conditions more than two thirds of the heat released by WGSR should be extracted from the first 20% of the reactor length. Sensitivity analysis of the WGSMR was also performed by changing the membranes permeance and surface area.
Keywords: IGCC; kombinirana plinsko-parna elektrarna z uplinjevalnikom; membrane reactor; membranski reaktor; reakcija vodnega plina; uplinjanje premoga; water-gas shift reaction